MEMBERI KESAKSIAN TENTANG KEBENARAN DI TENGAH BUDAYA FEAR OF MISSING OUT: REFLEKSI TEOLOGIS YOH 18:28-40 - Thomas Onggo Sumaryanto (Jurnal Teologi (Journal of Theology), 2021)
This paper is a theological reflection of John 18:28-40. This theological reflection is used as a basic principle of living in the midst of the digital era, especially to fight the culture of fear of missing out (FOMO). This passage is part of the story of the passion of Jesus Christ. In the Gospel of John, the story of Jesus before Pilate is dominated by Jesus’ dialogue with Pilate. In this dialogue, Jesus is shown as the King who proclaims the truth but Pilate rejects this testimony of Jesus. With a strong element of drama in the Gospel of John, the readers of the Gospel will be invited to believe that truth is God’s revelation that requires human participatory communication. The theological reflection that I want to emphasize is that dialogue with Jesus leads people to the depths to understand the mystery of God. But people who are caught up in FOMO have a shallow view of life. People who experience FOMO actually experience isolation and loneliness and then look for shortcuts. Deep dialogue with Jesus is necessary to gain spiritual strength to face isolation and loneliness in life.